Ketahanan Bank Mandiri Syariah melalui Uji NPF dan ROA pada Periode Krisis Global Tahun 2008-2016 dari Dampak Pertumbuhan Ekonomi, Inflasi, dan Suku Bunga - M. Shaiful Umam (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
Bank Syariah Mandiri is a banking institution established by Bank Mandiri. This study aims to analyze the effect of economic growth, inflation, and interest rates on the flexibility of Bank Mandiri Syariah as measured by ROA (return on assets) and NPF (bad performance). This research is a quantitative study with the independent variables of economic growth, inflation and interest rates. The dependent variable is the return on assets (ROA) and risk of financing (no financing is made). The results of this study indicate that: (1) the variable Economic Growth Rate (IPI) has a negative effect on the Return on Assets (ROA) of Bank Syariah Mandiri for the period 2008-2016; The Bank's Return on Assets (ROA) during the period 2008-2016 had a negative impact; (2) The inflation rate (CPI) has a negative effect on the return on assets (ROA) of Bank Syariah Mandiri during 2008-2016; (3) Interest rates (SBI) have a negative effect on return on assets of Bank Syariah Mandiri during 2008-2016 (ROA) does not have a significant negative effect; (4) Economic growth rate (IPI) has a negative effect on non-performing financing (NPF) of Bank Syariah Mandiri from 2008 to 2016; (5) The inflation rate (CPI) has a negative effect on Bank Syariah Mandiri 2008 - Non performing financing (NPF) 2016 has a negative impact; (6) Interest rates (SBI) will not have a significant negative effect on the Non-Performing Loan (NPF) of Bank Syariah Mandiri for the period 2008-2016.